Peran Ayah Dalam Pendidikan Anak Perspektif Al-Qur’an (Telaah Tafsir Ibnu Katsîr dan Al-Mishbâẖ) - Adawiyah, Rabiatul; Widayati, Romlah; Al-Ghifary, M. Ubaidillah (Jurnal Paedagogy, 2022)
This study aims to analyze the morals of fathers in educating children in the perspective of the Qur'an by studying Ibn Katsr's interpretation and al-Mishbâẖ's interpretation. This study uses a library research method using primary data of Ibnu Katsr's interpretation and al-Mishbâẖ's interpretation, secondary data in the form of pre-existing sources such as other supporting books related to the object being studied. The main steps of data analysis in this study begin with an inventory of the text in the form of verses, examine the text, look at the historical verses and look at the hadiths. Furthermore, it is interpreted objectively and described descriptively and then drawn some deductive conclusions. The results of this study indicate that the morals of fathers in educating children in the perspective of the Qur'an with the interpretation of Ibn Katsr and the interpretation of al-Mishbâẖ are wills, love for children with the call yâ bunayya (O my son), grateful, not burdensome to children and prospective in-laws, and pray.